2016
DOI: 10.3389/fmicb.2016.00038
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation, Biosorption of Phenanthrene and Its Trans-Membrane Transport by Massilia sp. WF1 and Phanerochaete chrysosporium

Abstract: Reducing phenanthrene (PHE) in the environment is critical to ecosystem and human health. Biodegradation, biosorption, and the trans-membrane transport mechanism of PHE by a novel strain, Massilia sp. WF1, and an extensively researched model fungus, Phanerochaete chrysosporium were investigated in aqueous solutions. Results showed that the PHE residual concentration decreased with incubation time and the data fitted well to a first-order kinetic equation, and the t1/2 of PHE degradation by WF1, spores, and myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…in PAH degradation in environmental samples, one study showed that Massilia sp. strain WF1 had high degradation ability and tolerance to PHE (Gu et al 2016). Additionally, Massilia seems to also tolerate metal contamination (Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…in PAH degradation in environmental samples, one study showed that Massilia sp. strain WF1 had high degradation ability and tolerance to PHE (Gu et al 2016). Additionally, Massilia seems to also tolerate metal contamination (Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Massilia spp. are reportedly phenanthrene degraders (38), and Bacillus spp. were dominant in the n-octadecane degradation consortia (7,39).…”
Section: Discussionmentioning
confidence: 99%
“…The first method has the following four stages: (a) formation of the cores of pellets when the bacteria join the cohesion of the spores, (b) bacterial growth and hyphae germination from the spores in the cores, (c) constantly packaging bacteria in the hyphae through the shear of water, and (d) formation of mycelium pellets when bacteria and hyphae become entire ball‐like systems. Compared to the coupled pellets produced through the second method, the first method exhibited a higher capacity to remove pollutants for fungi and bacteria (Gu et al., ). However, the operating conditions must be optimized to adjust to the environment.…”
Section: Two Types Of Pellets For the Treatment Of Polluted Watermentioning
confidence: 99%
“…Several studies investigated the specific organic pollutant removal mechanisms of the combination of pellets, bacteria, and fungi to identify the individual removal mechanism employed by bacteria, and fungi pellets for biosorption or biodegradation of the pollutants. For example, Gu studied the biodegradation and biosorption of coupled Massilia sp (Gu et al., ). WF1 and fungi pellets of Phanerochaete chrysosporium and found that WF1 had the ability to degrade phenanthrene, while the Phanerochaete chrysosporium can produce mycelia pellets.…”
Section: Two Types Of Pellets For the Treatment Of Polluted Watermentioning
confidence: 99%